Initiation zone of DNA replication at the aldolase B locus encompasses transcription promoter region. - Zhao, Y (1994)
Aldolase A (AldB) gene is one of the liver-specific genes, which is activated in the fetal stage. As a first step to investigate the functional relationship between transcription and DNA replication, we intended to determine the initiation zone of replication nearest to the AldB gene region. BrdU-labeled nascent DNA was obtained from G1/S arrested hepatoma cells at various times after entering S phase. Hybridization of the newly synthesized, BrdU-labeled DNA with probes corresponding to regions spanning about 26 Kb, revealed that replication zone locates within the AldB gene region. This result, together with the result of hybridization of nascent DNA obtained by alkaline sucrose density-gradient centrifugation, suggested that the initiation zone is located within a more defined region (about 1.0 Kb) containing AldB promoter. In the predicted initiation zone, a purine-rich element which shows high homology to known mammalian origin sequences and other replication components are found. Further, autonomously replicating activity of this initiation zone was examined by DNA transfection. The results showed that the predicted initiation zone confers replication initiation in Cos-1 cells.